The waterflow in the Matsalu National Park - Kumari, Erik (Wildfowl, 1962)
A brief survey of the wildfowl reserves of the Matsalu National Park, situated at the mouth of the R. Kasari on the west coast of Estonia, facing the Baltic Sea.